Finite Automata And Applications - Elfakhakhre, Nawara R.F. (2010)
A finite automaton can be considered as the simplest machine model in that the machine has a finite memory. Automaton terhingga (finite automaton) boleh dianggap sebagai suatu model mesin teringkas, yang mempunyai memori terhingga.